Conflict and Compromise in Evaluation Research: A Case Study - Chommie, Peter (1974)
As has been pointed out by a host of writers, a crucial issue in conducting evaluative or action type research is the problem of gearing an appropriate research design into the cogs of organizations, ensuring that once initiated the evaluation is in fact conducted according to the original design, and that the results of the study are utilized in policy formulations and ultimately in program development. The focus of this case study is on the major political and administrative problems and processes involved in planning, conducting, and utilizing the findings from a field experiment dealing with the relative effects of parole supervision as provided to a group of juvenile aged boys and girls